Experiência e esquema conceitual em Strawson - Nunes, Cristina de Moraes (2011)
In The Bounds of Sense, Strawson presents what he considers a major Kantian contribution to the analytic philosophy. This contribution corresponds to Kant‟s attempt to establish the general possible limits to the experience and therefore also to limit our use of concepts. According to the principle of significance, the limits of experience are limits to the significant use of concepts. In Individuals, Strawson develops the metaphysical project and takes into account many of the positive aspects found in Kant‟s theory, as it is the case of the empiricist principle of significance. In this metaphysical project, Strawson is interested in clarifying our thinking about the world this is made possible by the use of a single conceptual scheme. In the conceptual scheme the concepts are interconnected and these are the concepts that allow us to access things in the world. In his ontology a necessary condition for maintaining the conceptual scheme is the undisputed acceptance of the continued existence of some objects, Thus, Strawson is faced with the skeptic who doubts the continued existence of material bodies. The transcendental argument used in Individuals to show that skeptical doubt is incoherent he received criticism such as Barry Stroud. For Stroud the transcendental argument implies certain verificationism to assert the continued existence of particulars, but to accept the verificationism is to refute directly the skeptic, so that the transcendental argument becomes insufficient to refute skepticism. In Skepticism and Naturalism, Strawson accepts Stroud‟s criticism and he found in naturalism a way not to refute the skeptic, but just leave it aside, as it is natural to believe in the existence of material bodies and people. By embracing naturalism, Strawson gets closer of the realistic. He believes we can know things directly as they really are. This is possible because our sense perception is always permeated by concepts, so that, our sensitive knowledge is always conceptual. The concepts are learned in their practice of using, by observing the behavior of other users. Wherefore, when Strawson approaches Wittgenstein he gives a step ahead of Kant and he states that the concepts limit what we can know. Therefore, the basic features for a consistent conception of experience are agency and society and the limits to our knowledge are always set by the language.